Effect simultaneous delivery with P-glycoprotein inhibitor and nanoparticle administration of doxorubicin on cellular uptake and in vitro anticancer activity - Ozgur Esim; Meral Sarper; Cansel K. Ozkan; Sema Oren; Baris Baykal; Ayhan Savaser; Yalcin Ozkan (Elsevier, 2020)
Multidrug resistance (MDR) is the most common problem of inadequate therapeutic response in tumor cells. Many trials has been developed to overcome drug efflux by P-glycoprotein (P-gp). For instance, co-administration of a number of drugs called chemosensitizers or MDR modulators with a chemotherapeutic agent to inhibit drug efflux. But for optimal synergy, the drug and inhibitor combination may need to be temporally colocalized in the tumor cells. In this study, we encapsulated the Ver and Dox in PLGA nanoparticles to inhibit the P-gp drug efflux in breast cancer. Moreover, the effect of either Dox solution (DoxS), Dox nanoparticles (DoxNP), DoxS + VerS, DoxNP + VerS, DoxNP + VerNP or Dox-VerNP was evaluated. It was found that co administration of DoxNP with VerNP (70.76%) showed similar cellular uptake of Dox to Dox/Ver combination solution (70.62%). However it is observed that DoxNP + VerNP has the highest apoptotic activity (early apoptotic 13.52 ± 0.06%, late apoptotic 53.94 ± 0.15%) on human breast adenocarcinoma (MCF 7) cells. Hence, it is suggested that DoxNP + VerNP is a promising administration for tumor therapy. Keywords: Doxorubicin, Verapamil, P-glycoprotein, Nanoparticle